Value of contrast-enhanced ultrasound for vascular diseases of the liver - current indications and open questions: Übersicht = Stellenwert des kontrastverstärkten Ultraschalls bei Gefäßerkrankungen der Leber – aktuelle Indikationen und offene Fragen - Wiest, Isabella; Zadeh, Ehsan Safai; Görg, Christian; Teufel, Andreas; Michels, Guido; Dietrich, Christoph F. (Zeitschrift für Gastroenterologie, 2023)
Contrast-enhanced ultrasonography (CEUS) is a widely available and well-tolerated technique that can expand the diagnosis of a variety of vascular liver diseases. This paper presents an overview of the current possibilities of the use of CEUS in vascular liver diseases. Particularly where Doppler sonography has technical limitations, CEUS provides additional opportunities to visualize vascular thrombosis and other obstructions restricting blood flow. When CT or MRI contrast agents cannot be used because of severe allergy or renal insufficiency, CEUS can be a valuable diagnostic alternative and has demonstrated comparable diagnostic performance in at least some vascular liver diseases, such as portal vein thrombosis. In addition, CEUS works without radiation and, therefore, might be particularly suitable for young patients and children. This may be useful, for example, in congenital disorders such as persistent umbilical vein or preduodenal portal vein. Vascular liver disease is rare and comprehensive data are still lacking, but the available literature provides promising insights into potential new ways to study vascular liver disease. Although most studies are based on small sample sizes or even case reports, the high diagnostic utility is undisputed.
Artikel online veröffentlicht: 15. Dezember 2022
Gesehen am 10.06.2024